Menjaga Netralitas ASN dari Politisasi Birokrasi (Protecting The ASN Neutrality From Bureaucracy Politicization) - Gema Perdana (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2019)
The neutrality of ASN and the politicization of the bureaucracy are still issues that need to be addressed immediately. This paper discusses the history of ASN neutrality arrangements; the influence of the bureaucratic politicization toward the ASN neutrality; and the role of KASN in manifesting the ASN neutrality. This paper is a result of a normative legal research, using the historical approach and statute approach. This paper is intended to contribute on the formulation of the ASN management that is free from the political intervention and works solely for the benefit of the nation and the state. In its history, the ASN’s neutrality was highly influenced by the inclination of the legislators. The public officials, whether from a political background or independent, should not place the ASN as a tool to maintain their power. The new institution of the State Civil Apparatus Commission (KASN) is expected to be able to maintain the quality of the implementation of the merit system. Furthermore, the regulations are needed in order to restrict the access of public officials to conduct abuse of authority, also provide the access to strict supervision from the parties including the ASN’s internal in order to be able to report any form of intervention. AbstrakNetralitas ASN dan politisasi birokrasi masih menjadi permasalahan yang perlu segera diatasi. Tulisan ini membahas mengenai sejarah pengaturan netralitas ASN; pengaruh politisasi birokrasi terhadap netralitas ASN; dan peran KASN untuk mewujudkan netralitas ASN. Tulisan ini merupakan hasil penelitian hukum normatif (normative legal research), dengan menggunakan pendekatan sejarah (historical approach) dan peraturan perundang-undangan (statute approach). Tulisan ini bertujuan memberikan kontribusi dalam perumusan manajemen ASN yang bebas dari intervensi politik dan bekerja semata-mata untuk kepentingan bangsa dan negara. Dalam sejarahnya, netralitas ASN sangat dipengaruhi oleh keinginan dari pembentuk undang-undang. Pejabat publik, baik berasal dari politik ataupun independen, tidak seharusnya menempatkan ASN sebagai alat untuk mempertahankan kekuasaannya. Lembaga baru Komisi Aparatur Sipil Negara (KASN) diharapkan mampu menjaga kualitas pelaksanaan sistem merit. Selanjutnya, diperlukan regulasi dalam rangka pengetatan akses pejabat publik untuk menyalahgunakan kewenangan, serta memberikan akses pengawasan yang ketat dari para pihak termasuk internal ASN untuk dapat melaporkan segala bentuk intervensi.